Reverse-Payment Patent Settlements in the Pharmaceutical Industry: An Analysis of U.S. Antitrust Law and EU Competition Law. (March 2014) - Clancy, Michael; Geradin, Damien; Lazerow, Andrew
In the pharmaceutical industry, originator companies researching and developing new medicines typically obtain a range of patents to protect these medicines against generic competition. On the other side, generic suppliers seeking to enter the market will often challenge the validity of these patents or may simply launch their products, forcing the originators to bring litigation to enforce their patents and prevent the generics' entry. In the context of the corresponding litigation, the originators and generic suppliers often decide to enter into a settlement. While the settlement terms will vary from case to case, a number of settlements have involved a payment made from the patent holder (the originator) to the accused infringer (the generic supplier) in order to settle the dispute (reverse-payment patent settlements). Against this background, this paper seeks to analyze the compatibility of such settlements under U.S. antitrust law and EU competition law drawing on recent cases.